Semi-continuous approach for the study of impacts on woven composite laminates: Modeling interlaminar behavior with a specific interface element. (January 2015) - Navarro, P.; Pascal, F.; Aubry, J.; Marguet, S.; Ferrero, J.F.; Lemaire, S.; Rauch, P.
Abstract: This paper investigates impacts on sandwich structures made up of a thin woven composite skin and polyetherimide foam core. A semi-continuous Finite Elements explicit modeling was chosen to represent the response of the woven skin made of plies with different orientations. The plies are modeled with specific woven elements, and are bonded with a new damageable shell-to-shell interface element. The modeling strategy is validated by representing static bending, low velocity impacts and medium velocity oblique impacts. The presented approach is accurate enough to predict the size and the shape of the damage for the woven composite laminate. Highlights: Impacts on sandwich structures made up of a woven composite skins are investigated. A FE modeling is proposed for the skin made of plies with different orientations. The plies are modeled with specific woven elements. The plies are bonded with a new damageable shell-to-shell interface element. The damage size and shape of the woven composite laminates are accurately represented.